Efektivitas Patroli Anggota Kepolisian Dalam Upaya Penegakan Hukum Terhadap Pencegahan Tindak Pidana Pencurian Di Wilayah Hukum Kepolisian Sektor Sungailiat - Leyla Dana; Toni; Rio Armanda Agustian (CV. Multi Kreasi Media, 2025)
The Indonesian National Police (Polri) plays a crucial role in maintaining public order and enforcing the law. Polri carries out two main duties: preventive and repressive tasks. Preventive duties include regular and targeted patrols to prevent criminal acts. However, despite these preventive measures, theft cases continue to occur frequently and have increased in the jurisdiction of the Sungailiat Sector Police (Polsek). Data from 2021 to 2023 show a significant rise in theft cases. Therefore, more effective patrol strategies are needed to prevent theft crimes and enhance public safety. This study aims to analyze the effectiveness of police patrols in law enforcement and crime prevention, as well as to identify the challenges faced in conducting patrols within the jurisdiction of Sungailiat Sector Police. This research employs an empirical method with a qualitative approach. Data collection techniques include interviews and documentation. The findings indicate that while the patrols conducted by Sungailiat Sector Police have been implemented well, efforts to prevent theft crimes are still considered ineffective. Several factors hinder patrol implementation, including a limited number of personnel and low community participation in maintaining security.